Effect of intellectual intelligence , emotional intelligence , intelligence and spiritual organization commitment to the performance of provincial auditor BPK Riau - Juliana Sitompul; Azwir Nasir; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of intellectual, emotional intelligence , spiritualintelligence and organizational commitment to performance BPK auditors Riau province .The research method used is a research method deskriktif the survey approach . The collected data obtained through questionnaires , with 54 auditors . Processing and analyzing the data using the classical assumption test after test validity and reliability , then drawn a conclusion by using multiple regression statistical test . with the aid of a computer program that SPSS version 17.00.The results of hypothesis testing one and five received . This illustrates that the intellectual, emotional intelligence , spiritual intelligence and organizational commitment and a significant positive effect on the Performance Auditor . With significant values of 0.003 , 0.007 , 0.022 and 0.01 . Coefficient of determination for themselves by 30.7 % , which means that the variable intellectual, emotional intelligence , spiritual intelligence and organizational commitment to performance auditor may explain the variable performance BPK auditors at 30.7 % and the remaining 69.3 % is influenced by factors others are not examined in this research .Keywords : Intellectual Intelligence , Emotional Intelligence , Spiritual Intelligence , Organizational Commitment , Performance Auditor BPK Riau Province .